Rare Case of Cystic Lymphangioma Transforming Into Lymphangiosarcoma: A Case Report - Yu, Huili; Mao, Qinxiang; Zhou, Lingyan; Li, Jiawei; Xu, Xunhua (Frontiers in Oncology, 2022)
Cystic lymphangioma (CL) is a rare benign tumor that mainly occurs in the neck and axilla and usually occurs in children, whereas lymphangiosarcoma (LAS) is a rare invasive tumor, usually secondary to chronic lymphedema caused by various causes, with a rare malignant transformation from CL. We presented the case of a 63-year-old woman who underwent four surgical excisions for multiple recurrence of CL in the right groin. The changes of imaging and pathological examination revealed the unusual process of its gradual malignant transformation into LAS. We followed up the patient for 16 years, and she eventually died of LAS complications.